Penanganan Kasus Asusila Melalui Hukum Adat Bali Diluar Hukum Pidana KUHP - Mursyidi, Mursyidi; Anam, Nurul; Ali, Mufti (Syura: Journal of Law, 2024)
Indonesia is a nation whose people have diverse tribes, races, religions and customs spread across cities and villages. This diversity is a wealth and potential owned by the Indonesian nation. In community life, law and society are two things that cannot be separated. Ibi ius ibi societas, where there is society, there is law. Therefore, a legal rule is needed to regulate community life in order to achieve public order. These legal rules are written and unwritten. Applicable nationally and regionally, in the field of public law and private law. The purpose of this study is How is the legal process to ensnare perpetrators of immoral cases both under customary law and criminal law based on the Criminal Code in Bali? What is the cause of criminal law based on the Criminal Code not being able to touch immoral cases that occur in Bali. This study uses a qualitative approach with a library method where the data comes from books and articles and related websites. The results show that the legal process for the perpetrators of immoral acts that occurred in Banjar Bia Bali between WL (48 years old) and MJ (60 years old) who came from Sukawati Village was resolved by the village peace judge in Keramas Village because they were legally proven guilty. The reason criminal law cannot touch the Balinese community, especially the wives and husbands of the perpetrators of immoral acts is proven by the absence of complaints or reports to the local police because the Balinese indigenous community believes in the existence of ancestral spirits who are their guides and guides in life.